Ø§Ù„Ø§ØªØ¬Ø§Ù‡Ø§Øª Ø§Ù„ØØ¯ÙŠØ«Ø© Ù„ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© ÙÙŠ Ø§Ù„Ø¹ØµØ± Ø§Ù„Ø±Ù‚Ù…ÙŠ 4.0 - Wijaya, Jaka Imam Mahesa (Lughawiyah: Journal of Arabic Education and Linguistics, 2019)
This article discusses about the use of technology as an Arabic teaching trend in 4.0 era. Students can use various online programs by using netbook or smartphone everywhere and anytime easily. The trend means that teaching and learning Arabic can be done anytime they want and wherever they go because what they need is just network and online connection.